Folie et Société: eroding the body–mind relationship via dysfunctional paternalistic systems - Hudson, Matt; Chaudhary, Nazish Idrees; Nordstrom, Curtis (Frontiers in Psychology, 2024)
This theoretical perspective examines the proposition of shared complex trauma between a parent and child, arising from blurred relational boundaries and societal oppression, leading to inequality both at home and within the larger paternalistic system of society. Specifically, the focus is on living within a paternalistic, authoritarian system where rules are unjust, demanding obedience and compliance without questioning the behaviors of the authority. Individuals growing up in these circumstances are subject to adverse and emotionally overwhelming experiences, which lead to the creation of emotional memory images (EMIs). The delusion in which the child is caught up becomes a reality for the child as time passes. This phenomenon is recognized in psychiatry as “Folie à deux” (the madness of two or more) at the micro level, and “Folie et Société” (the madness of society) on the macro level. Complex trauma, derived from a child’s exposure to multiple adverse events, can erode the mind–body relationship, impacting both mental and physical health. These traumatic experiences in early childhood can manifest as body-focused disorders in adolescents, prevailing throughout adulthood if left unattended. This article provides a theoretical perspective on dealing with the dissociation and chronic stress related to oppressive and authoritarian family systems. The broader implications of this article include highlighting the psychophysiological underpinnings of complex trauma, the relationship of a highly oppressive paternalistic authoritarian system imposed on children and adolescents, and the role of Split-Second Unlearning as a therapeutic intervention to clear EMIs and improve overall health outcomes.